Condicionantes sobre a prática educativa: estudo comparativo da aplicação de sequências didáticas por professores de química em formação inicial e fundamentadas no modelo topológico de ensino - Pedroso, João Victor Callera [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Currently, speeches that reduce schoolwork to teaching work, in addition to considering the action of teacher individualized and reduced only in the classroom, are often propagated by school management sectors and in sections of the population. These are some of the concepts that have intensified educational policies called large-scale assessments, especially those of the second and third generation, being mechanisms that further accentuate this individual accountability. In this way, this work aims to identify, compare and elucidate how the conditioning factors acted on the model of and continuity property during the Didactic Sequences applications, built and based on the Topological Teaching Model, by chemistry teachers in initial training at two State schools in São Paulo, which model of two totally model of school realities. In order to achieve these objectives, data were collected from two mappings made about two case studies that occurred within the scope of PIBID on the model of applying in SD, segmenting it into episodes and timing the time of activities. With these data available, a “comparative case study” was carried out, which identified two factors that interfered with the continuity of educational action in each school: i) institutional context and ii) target audience – resulting in an abandonment of MTE properties in one school and a good development for another. This work helps both to raise awareness about the plot that surrounds the teaching and learning process and to improve the search for formative actions aimed at raising the political, social and ethical awareness of teachers about their work.

Atualmente, discursos que reduzem o trabalho escolar ao trabalho docente, além de considerar a ação do professor individualizada e reduzida somente a sala de aula são propagados muitas vezes por setores de gestão escolar e em parcelas da população. Essas são algumas das concepções que intensificaram as políticas educacionais chamadas de avaliações de larga escala, principalmente aquelas de segunda e terceira geração, sendo mecanismos que acentuam mais essa responsabilização individual. Desta forma, este trabalho objetiva identificar, comparar e elucidar de que modo os condicionantes atuaram sobre a propriedade de contexto e continuidade durante as aplicações de Sequências Didáticas, construídas e fundamentadas no Modelo Topológico de Ensino, por professores de Química em formação inicial em duas escolas Estaduais de São Paulo, que apresentam duas realidades escolares totalmente diferentes. Para a consecução desses objetivos então, foram coletados os dados de dois mapeamentos feitos acerca de dois estudos de caso que ocorreram no âmbito do PIBID sobre o processo de aplicação de uma SD, segmentando-a em episódios e cronometrando o tempo das atividades. Com esses dados disponíveis, foi realizado um “estudo comparativo de casos” que identificou dois fatores que interferiram na continuidade da ação educativa em cada escola: i) contexto institucional e ii) público-alvo – resultando em um abandono das propriedades do MTE em uma escola e em um bom desenvolvimento para outra. Este trabalho auxilia tanto para a conscientização sobre a trama que está envolta do processo de ensino e aprendizagem quanto numa melhora na busca por ações formativas objetivando a conscientização política, social e ética dos docentes acerca de seu trabalho.
Constraints on educational practice: a comparative study of the application of didactic sequences by chemistry teachers in initial formation and based on the topological teaching model
Keywords: Constraints; Teaching work; Didactic sequence; Topological model of teaching; Teacher Education; Condicionantes; Trabalho docente; Sequência didática; Modelo topológico de ensino; PIBID; Formação de professores